2001
DOI: 10.1016/s0885-3924(01)00247-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceived Competence of Home Care Nurses in Pain Management

Abstract: This national mail survey assessed pain-related knowledge and subjective competence of a random sample of home care nurses across the United States. Other study objectives were to examine the relationship between nurse characteristics, knowledge and perceived competence, and assess continuing education practices. On average, the 1236 nurses scored only 56% of the items correctly, demonstrating stronger knowledge in pain assessment than treatment. Respondents reported most confidence in patient and family commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 36 publications
(64 reference statements)
3
35
2
1
Order By: Relevance
“…20 The nurses responded correctly to only 56% of the scored items in a pain assessment and management survey; the highest knowledge was demonstrated in pain assessment. A study evaluating nurses' knowledge of pain in elders revealed a similarly significant knowledge deficit, particularly in terms of appropriate use of analgesics in elders.…”
Section: Review Of the Pain Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…20 The nurses responded correctly to only 56% of the scored items in a pain assessment and management survey; the highest knowledge was demonstrated in pain assessment. A study evaluating nurses' knowledge of pain in elders revealed a similarly significant knowledge deficit, particularly in terms of appropriate use of analgesics in elders.…”
Section: Review Of the Pain Literaturementioning
confidence: 94%
“…12, [19][20][21][22] This is of major concern because without a sound understanding of assessment and the use of pharmacologic and nonpharmacologic interventions, nurses cannot advocate for appropriate pain treatment on behalf of their patients.…”
Section: Review Of the Pain Literaturementioning
confidence: 99%
“…Other HCPs have reported over-and underestimations of their performance (Jansen et al, 1995;Tracey, Arroll, Barham, & Richmond, 1997;Latif et al, 1998;Glajchen & Bookbinder, 2001;Barnsley et al, 2004), suggesting others may require support in their pursuit of self-awareness of competence. Social desirability and overconfidence, or a lack of confidence were factors interfering with reporting true performance (Jansen et al, 1995;Latif et al, 1998;Glajchen & Bookbinder, 2001;Barnsley et al, 2004).…”
Section: Influence Of Training and Medication Reviews On Self-assessementioning
confidence: 99%
“…Il comportait près de 200 questions, dont un module dédié au traitement de la douleur. Ce module était composé de 29 questions utilisées dans d'autres pays pour évaluer le niveau de connaissance des infirmiers, ainsi que d'une vignette clinique [17,18]. Cette vignette portait sur la prescription en première intention d'un antalgique de niveau 3 pour un patient en phase terminale atteint d'un cancer pulmonaire et ayant une douleur intense, c'est-à-dire forte et persistante, sans doute due à des compressions tumorales ou métastatiques.…”
Section: Questionnaireunclassified